REDUCTION OF MEAN SEA LEVEL DEPTH BASED ON TIDE GAUGE DISTANCE-DEPENDENT AT SUNGAI DINDING, LUMUT - N. A. S. Ismail; A. H. M. Din; A. H. M. Din; M. H. Hamden; N. A. Zulkifli; K. M. Idris (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
Tidal correction is vital in shipborne bathymetric survey. This research uses two different tide gauge stations as tidal corrections to reduce the sounding depth. The tide corrections used are from the tidal observation at the survey site and the nearest tide gauge established by the Department of Survey and Mapping Malaysia (DSMM). The issue that may affect the results is the distance between the tide station used for corrections and the survey site. Are the results obtained by these two distinct tide corrections comparable? And if not, what are the cause for any discrepancies in the results? Thus, this research aims to assess the reduction of Mean Sea Level (MSL) depth using the bathymetric survey data at Sungai Dinding, Lumut relative to two different tide gauge with different distance to the survey site. The two distinct tidal corrections are observed and analysed separately. The tidal data are processed using HYDROpro software, followed by the analysis of the bathymetric plan and the computation of Root Mean Square Deviation (RMSD). The results of different tide corrections are then compared. Furthermore, the reliability of bathymetry data relative to two tide gauges at different distances is also evaluated. For various reasons, the tidal corrections shed new light on the accuracy of depth reduction in the Sungai Dinding area. Besides, using two different tide gauges: on-site tide gauge observation and the nearest DSMM tide gauge (Lumut), provide an insight into the reliability of bathymetry data by comparing the depth derived relative to two different tide gauges at different distances from the survey site. The findings are instructive for future depth reduction, as they will allow for more practical application of the tide corrections. Optimistically, this study will raise awareness of the importance of tide station location in the bathymetry survey area.